FORMATION OF E-CULTURE IN THE INSTITUTIONALIZATION OF INFORMATION AND COMMUNICATION SPHERES OF SOCIETY - Литовченко, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article considers the specifics of the formation of e-culture in the institutionalization of information and communication spheres of society.